1981
DOI: 10.1104/pp.68.2.358
|View full text |Cite
|
Sign up to set email alerts
|

Host-Pathogen Interactions

Abstract: A previously unrecognized phytoalexin has been isolated from soybean cotyledons that had been infected with bacteria or exposed to ultraviolet light. The phytoalexin has been purified to homogeneity by silica gel flash chromatography and high pressure liquid chromatography. It has been structurally characterized by its ultraviolet, circular dichroism and nuclear magnetic resonance spectra, polarimetry, and its mass spectrometric fragmentation pattern. The phytoalexin, (6aS,llaS)-3,6a,9-trihydroxypterocarpan, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The Gram-negative bacterium E. carotovora has been shown to elicit the accumulation of pterocarpan phytoalexins in wounded soybean cotyledons (33). Ninety-five per cent of this elicitor activity was abolished by killing the bacteria with heat treatments or antibiotics (13).…”
mentioning
confidence: 99%
“…The Gram-negative bacterium E. carotovora has been shown to elicit the accumulation of pterocarpan phytoalexins in wounded soybean cotyledons (33). Ninety-five per cent of this elicitor activity was abolished by killing the bacteria with heat treatments or antibiotics (13).…”
mentioning
confidence: 99%
“…Furthermore, the maximum amount of phytoalexins induced by the decagalacturonide appeared to be approximately half of the maximum amount induced by the ,3-glucan elicitor and equivalent to that induced by PGA lyase (7). The amount of the phytoalexin, glycinol, induced by 5 ug/ cotyledon of the decagalacturonide was estimated to be approximately 100 Mg/ml (7), which is a concentration previously shown to significantly inhibit the growth of various microorganisms (36). Experiments in which a decagalacturonide-rich fraction was assayed in the presence of fractions rich in other specific sized oligogalacturonides demonstrated that these fractions modified the elicitor activity of the decagalacturonide (Table VII).…”
Section: Discussionmentioning
confidence: 99%
“…This paper is based on part of a Ph.D. thesis presented to the University of Colorado toalexins (1, 1 1). Phytoalexins are a diverse group of compounds of low mol wt that have broad antibiotic activity against many prokaryotic and eukaryotic organisms (32,36). In some hostpathogen combinations, phytoalexins accumulate at the site of attempted infection rapidly enough and in sufficient concentration to prevent further growth of the invading microorganism (19,24).…”
mentioning
confidence: 99%
“…Among isoflavonoids, glyceollins have a characteristic tetracyclic structure and are known as pterocarpan. Glyceollins are synthesized via glycinol as the major phytoalexin in soybeans (Glycine max) and are known for their antibiotic and antitumor activities (Boué et al 2009;Salvo et al 2006;Weinstein et al 1981). Medicarpin is another pterocarpan-type phytoalexin that is distributed in various legume lineages, including Canavalia, Cicer, Glycyrrhiza, Medicago, Melilotus, and Trifolium.…”
mentioning
confidence: 99%